Assessment of the Achievement Level Kandri Tourism Village, Gunungpati District, Semarang City - Abhi Kurniawan; Rina Kurniati (TATALOKA, 2023)
Kandri Tourism Village was founded in 2012, so it has been a tourism village for 9 years. In their development, in 2016 Kandri Tourism Village was classified as a "Pioneering Tourism Village" and in 2019 increased to a "Developing Tourism Village" based on data from the Central Java Province Tourism Village Assessment. These facts became the right momentum for researching the assessment of the Kandri Tourism Village program. The purpose of this study is to assess the achievement level of the Kandri Tourism Village which has been carried out until now. The research method uses a quantitative approach, while the sampling method uses simple random sampling and purposive sampling with a 100% response rate of the questionnaire, and is analyzed using scoring analysis techniques. The analysis process begins with the respondent giving a score to the tourism village variable, then recapitulating and calculating to get the average score for each variable, then summing it up to find out the final result of achievement level. The results showed that the achievement level of the Kandri Tourism Village program was 154 and was included in the "Developed Tourism Village" category. The benefit of this research is that it can provide information related to the achievement level of the Kandri Tourism Village program which is currently included in the "Developed Tourism Village" category and recommendations for improvement and development starting from the Aspects of Tourist Attractions, Accessibility, Infrastructure, Institutions, and Society in Kandri Tourism Village, so that the information and recommendations can be input for improving Kandri Tourism Village to be even better in the future.